A Study of the Deformation, Network, and Aging of Polyethylene Oxide Films by Infrared Spectroscopy and Calorimetric Measurements. (21st February 2012) - Bergeron, Carl; Perrier, Etienne; Potier, Aymeric; Delmas, Geneviève
Abstract : The calorimetric and infrared (IR) spectroscopy measurements of polyethylene oxide (PEO) are used to evaluate the deformation and relaxation that films experience during a temperature cycle (30°C–90°C–30°C). After melting, the intensity of some bands decreases by 10 to 70%. During the temperature cycle, the C–O band in the 1100 cm −1 region and the C–C–O deformation bands at 650 and 500 cm −1 show some new features. A network of cooperative oxygen-hydrogen interactions between the PEO chains form in films with special history, namely, in thermally treated films, in thin films prepared from gel forming solutions, and in thick films after aging. The interchain interaction network is suggested from the IR absorption bands in the 1200 and 900 cm −1 region and also from small bands at 1144 and 956 cm −1 . The network seems absent or reduced in thin films. IR spectroscopy appears a sensitive technique to study chain conformations in PEO films and in other materials where order, disorder, and the formation of intermolecular interactions coexist.